SIKAP, PENGAMBILAN KEPUTUSAN DAN KEPUASAN KONSUMEN TERHADAP AGROINDUSTRI PIE PISANG DI KOTA BANDAR LAMPUNG - Wayan Elpa Andela; Teguh Endaryanto; Rabiatul Adawiyah (Lampung University, 2020)
This study aims to determine consumer characteristics, attitudes, decision-making processes, and customer satisfaction towards banana pie at YA and JB. The research samples were 66 people selected by accidental sampling. The first and third objectives were analyzed descriptively, the second objective was analyzed using the Multiatribut Fishbein model, and the fourth objective was analyzed using Costumer Statisfaction Index (CSI) and Importance Performance Analysis (IPA). The results showed that the characteristics of consumers of banana pie were dominated by female 18-30 years old who earned Rp1,500,000.00 - Rp2,500,000.00/month. The frequency of buying banana pie on average was once a week. The consumer decision making process on purchasing banana pie, at YA and JB was the same, namely the introduction of needs, information seeking, evaluation of alternatives, purchasing decisions, and post-purchase evaluation. Consumers of banana pie at JB gave an attitude value of 178.40, those at YA gave an attitude value of 180. The satisfaction level of banana pie consumers at JB was 77.86% and 78.76% at YA, both were included in the satisfied category. The attribute of banana pie that was needed to be improved at JB was the expire date, whereas there was no attribute needed to be improved at YA. Key words : Attitude, CSI, IPA, purchasing decisions